Boron Doped TiO2 For The Photodegradation of 4-nitrophenol: Optimization of The Doping Parameters - Nazlı Türkten; Dila Kaya; Zekiye Çınar (Hittite Journal of Science and Engineering, 2020)
In this work we prepared boron doped TiO2 (B-TiO2) photocatalysts and evaluated their photocatalytic activity for the degradation of our model organic pollutant, 4-nitrophenol (4-NP). The photocatalysts were prepared using wet impregnation method with different calcination times, calcination temperatures and dopant amounts in order to determine the optimum parameters. The degradation of the pollutant was carried out in a specially designed degradation chamber and characterized by UV-Vis spectrophotometry. The degradation kinetics were evaluated with pseudo-first order kinetics by comparing rate constants and half-lives of various photocatalytic reactions. It was found that the highest removal rate was obtained for 0.50 % boron doping with calcination at 450°C for 3 hours. The results showed that TiO2 could be doped with boron, which is in abundance in our country, and used for the photocatalytic degradation of a toxic pollutant in water. The promising results for the organic matter removal could pave the way for further studies of environmental applications.